2018
DOI: 10.1016/j.tra.2017.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the impact of a real world cooperative-ITS deployment across multiple cities

Abstract: Cooperative Intelligent Transport Systems (C-ITS) -Connected Vehicle Technology in the USA -where vehicle and roadside infrastructure communicates to deliver more intelligent traffic management, is one of a range of ITS technologies emerging as a key component in pursuit of the wider objectives of improved urban mobility. This paper presents the Compass4D project, which deployed a C-ITS system in seven European cities and coordinated the common evaluation of the technology for three services focusing specifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…This adds additional complexity to road vehicle automation with the requirement for vehicle to vehicle and vehicle to infrastructure communications. It is thus imperative that the automated vehicle research community and those that are undertaking the development and proving of Connected ITS work closely together to solve this safety-critical issue (Edwards et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This adds additional complexity to road vehicle automation with the requirement for vehicle to vehicle and vehicle to infrastructure communications. It is thus imperative that the automated vehicle research community and those that are undertaking the development and proving of Connected ITS work closely together to solve this safety-critical issue (Edwards et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This would require the L3 AV system to be able to detect the stationary red vehicle blocking the road ahead at a long distance in advance (268.2 m when travelling at 30mph and 536.4 m when travelling at 60mph). In order to achieve this, it is imperative to design and develop user-friendly automated vehicles that are cooperative and connected 12 , 18 , 57 , 58 .…”
Section: Discussionmentioning
confidence: 99%
“…Implications of C-ITS development on safety and security was investigated in [363,364]. The impact of C-ITS adoption at a city scale was analyzed in [365], where potential benefits in terms of energy efficiency and environmental effects were quantified. Meng et al [366] reported some technological aspects required for the implementation of C-ITS.…”
Section: Cooperative Intelligent Transportation Systemsmentioning
confidence: 99%